2015
DOI: 10.1002/trtr.1363
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Culturally Relevant Texts With Kindergartners and Their Families

Abstract: This article shares a monthly curricular model that can help teachers and families bridge the gap between home and school by using literature and response inspired from the cultures in the classroom. Integrating culturally responsive texts and family response journals into the classroom and the home can help children, their families, and peers make critical connections to the literature as well as understand diversity as a productive resource. This yearlong curriculum model took place in a diverse kindergarten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The students began to discover their cultural identities by learning about their families’ origins, information about their names, and sharing their own and families’ characteristics. In their study of the Family Backpack Project, Schrodt, Fain, and Hasty (2015) found that kindergartners were able to empathize with the tribulations of diverse characters in the books they were reading. Students were able to engage in discussions about the characters with their family members and teachers at school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students began to discover their cultural identities by learning about their families’ origins, information about their names, and sharing their own and families’ characteristics. In their study of the Family Backpack Project, Schrodt, Fain, and Hasty (2015) found that kindergartners were able to empathize with the tribulations of diverse characters in the books they were reading. Students were able to engage in discussions about the characters with their family members and teachers at school.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the research of Martens et al (2015) suggested the importance of facilitating discussions about culture with primary students while helping students learn about small actions they can take to promote social activism. On the other hand, Schrodt et al (2015) showed that primary students are able to begin developing their own perspectives about acceptance and cultural individuality through discussions facilitated by a more knowledgeable other.…”
Section: Resultsmentioning
confidence: 99%
“…The data from this Teaching Tip come from an action research project Katie conducted while working at Acorn Academy, a small suburban private school in the American South with an explicit commitment to student diversity (see Schrodt et al, 2015). Participants included seven boys and seven girls ages 5–6 with diverse racial, ethnic, linguistic, and socioeconomic backgrounds: three African American students, one Jamaican American student, one Sudanese immigrant student who spoke Arabic at home, two Honduran immigrant students who spoke Spanish at home, one adopted student from Guatemala, one adopted student from Russia, and four white and monolingual English‐speaking students.…”
Section: Context Of Data Collectionmentioning
confidence: 99%
“…As a small institution in a new immigrant destination region, Acorn Academy had limited infrastructure for a formal bilingual curriculum, but the schools’ commitment to diversity empowered Katie to make space for multilingualism within the context of a culturally responsive curriculum (see Schrodt et al, 2015). Now colleagues at the same university, Janna, who researches teacher language ideologies, joined Katie in retrospective reflection on her teaching experience for this Teaching Tip.…”
Section: Context Of Data Collectionmentioning
confidence: 99%
“…Protacio and Edwards ( 2015 ) involved immigrant parents in planning a sharing time presentation in their children ' s first-grade classroom. Schrodt, Fain, and Hasty ( 2015 ) used culturally relevant texts to work with kindergartners and their families through book sharing and journaling. Engaging parents and students in goal-oriented activities helps them invest more in students' academic success.…”
Section: Design Goal-oriented Involvement Activitiesmentioning
confidence: 99%